An Equilibrium Model of General Practitioner Payment Schemes1. Issue 286 (1st July 2013) - Wright, Donald J.
<x xml:space="preserve">Abstract</x> In an environment where GPs are of differing quality and heterogeneous patients have different preferences for quality, it is shown that fee‐for‐service coupled with balance billing is a superior payment scheme to just fee‐for‐service or capitation payments as it generates an efficient allocation of GPs between high and low quality and an efficient allocation of patients between GPs. Where patients have more than one condition it is shown that fee‐for‐service allows patients to seek treatment from GPs of differing quality conditional on the medical condition they have.